Transformace baskického nacionalismu v průběhu 20. století - Pavla Andršová (AntropoWebzin, 2016)
Basque nationalism is a phenomenon thatemerged at the end of the 19th century and remainsalive until today. It had its ups and downs in thecourse of the 20th century, and during this period itchanged the way it manifested itself. This article introduces Basque nationalism, along with the circumstances and architects of its origin. It focuses primarily on the transformation of Basque nationalism and onthe changes in its form and ideological orientation according to the development of the Basque Country, orSpain as the case may be, from the end of the 19th century up to the present day. These changes are linked tothe transformation of Basque society itself and of theway that the Basque national identity is being constructed. At the same time, we can observe a refusalof the traditional conception of Basque nationality thatwas typical of the first nationalists.